Neural precursor cell delivery induces acute post-ischemic cerebroprotection, but fails to promote long-term stroke recovery in hyperlipidemic mice due to mechanisms that include pro-inflammatory responses associated with brain hemorrhages - Dongpei Yin; Chen Wang; Yachao Qi; Ya-Chao Wang; Nina Hagemann; Ayan Mohamud Yusuf; Egor Dzyubenko; Britta Kaltwasser; Tobias Tertel; Bernd Giebel; Matthias Gunzer; Aurel Popa-Wagner; et al. (Journal of Neuroinflammation, 2023)
Abstract Background The intravenous delivery of adult neural precursor cells (NPC) has shown promising results in enabling cerebroprotection, brain tissue remodeling, and neurological recovery in young, healthy stroke mice. However, the translation of cell-based therapies to clinical settings has encountered challenges. It remained unclear if adult NPCs could induce brain tissue remodeling and recovery in mice with hyperlipidemia, a prevalent vascular risk factor in stroke patients. Methods Male mice on a normal (regular) diet or on cholesterol-rich Western diet were exposed to 30 min intraluminal middle cerebral artery occlusion (MCAO). Vehicle or 106 NPCs were intravenously administered immediately after reperfusion, at 3 day and 7 day post-MCAO. Neurological recovery was evaluated using the Clark score, Rotarod and tight rope tests over up to 56 days. Histochemistry and light sheet microscopy were used to examine ischemic injury and brain tissue remodeling. Immunological responses in peripheral blood and brain were analyzed through flow cytometry. Results NPC administration reduced infarct volume, blood–brain barrier permeability and the brain infiltration of neutrophils, monocytes, T cells and NK cells in the acute stroke phase in both normolipidemic and hyperlipidemic mice, but increased brain hemorrhage formation and neutrophil, monocyte and CD4+ and CD8+ T cell counts and activation in the blood of hyperlipidemic mice. While neurological deficits in hyperlipidemic mice were reduced by NPCs at 3 day post-MCAO, NPCs did not improve neurological deficits at later timepoints. Besides, NPCs did not influence microglia/macrophage abundance and activation (assessed by morphology analysis), astroglial scar formation, microvascular length or branching point density (evaluated using light sheet microscopy), long-term neuronal survival or brain atrophy in hyperlipidemic mice. Conclusions Intravenously administered NPCs did not have persistent effects on post-ischemic neurological recovery and brain remodeling in hyperlipidemic mice. These findings highlight the necessity of rigorous investigations in vascular risk factor models to fully assess the long-term restorative effects of cell-based therapies. Without comprehensive studies in such models, the clinical potential of cell-based therapies cannot be definitely determined.